Awareness of colorectal cancer among public in Asir region - Mohammad Nassir Al-Sharif; Khalid Ali Fayi; Abdulsalam Ali Alobaidi; Bader Awadh Alshamrani (Journal of Family Medicine and Primary Care, 2018)
Introduction: Colorectal cancer (CRC) has different forms of colon cancer or rectal cancer. CRCs are often considered together because they possess many similar features. A severe form of the disease with higher mortality rate increases with increase in age. The most common CRC risk factors include smoking, diabetes, and obesity. This study aims to evaluate the awareness of CRC in a random population of Asir region and to identify the subpopulation that can be recipients of awareness and screening programs. Material and Methods: Cross-sectional nonprobable random sampling study using a self-administered questionnaire survey which was employed to include healthy males and females from Asir region. The questionnaire included ten questions in Arabic language and data were categorized according to gender, marital status, age, and level of education to determine whether these demographic groups possess difference in knowledge about CRC. Results: Most of the respondents (51% and 71.6%) knew what is colon and rectum. About 33.8% know the correct function of the colon while 22.5% know the correct incidence and 22.1% know the correct time of screening for CRC. Very few respondents know the symptoms, risks, and screening modalities of CRC.Pearson's Chi-square test was employed to evaluate the differences in responses in four demographic categories of the study population. P <0.05 was considered as statistically significant Conclusions: Single less educated males lack knowledge of CRC. In addition, there is very low awareness of CRC symptoms, risk factors, and screening modalities among the entire surveyed population.